SELF-REGULATED LEARNING SKILLS OF ELEMENTARY SCHOOL TEACHER EDUCATION STUDENTS DURING ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Aynin Mashfufah; Ika Lia Novenda (Jurnal Pendidikan Humaniora, 2022)
Abstract: The study aims to investigate the self-regulated learning skills of Primary School Teacher Education students during online learning and explore the relationships between each indicator in SRL skills. Descriptive analysis shows that students highly appreciate the assignments because of their intrinsic and extrinsic motivations. Nevertheless, students lack confidence, especially in mastering content that is complex. Most students have observed and managed the strategies in finding and learning information. The appreciation for tasks was positively correlated with confidence in learning as well as strategies in searching and studying information. Similarly, confidence in learning is positively correlated with strategies in searching and studying information. Abstrak: Penelitian ini bertujuan untuk mengetahui keterampilan belajar mandiri siswa Pendidikan Guru Sekolah Dasar selama pembelajaran online dan mengeksplorasi hubungan antara masing-masing indikator dalam keterampilan SRL. Analisis deskriptif menunjukkan bahwa siswa sangat menghargai tugas karena motivasi intrinsik dan ekstrinsik mereka. Meskipun demikian, siswa kurang percaya diri, terutama dalam menguasai materi yang kompleks. Sebagian besar siswa telah mengamati dan mengelola strategi dalam mencari dan mempelajari informasi. Apresiasi terhadap tugas berkorelasi positif dengan kepercayaan diri dalam belajar serta strategi dalam mencari dan mempelajari informasi. Demikian pula, kepercayaan diri dalam belajar berkorelasi positif dengan strategi dalam mencari dan mempelajari informasi.